2021
DOI: 10.1115/1.4048907
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of Ultra-Wet Methane Combustion Technique for Power Generation

Abstract: Using steam as heat carrier and working media has merits to increase electric efficiency up to 60% and decrease NOx emission to single-digit compared to dry gas turbine cycles. These attribute to the physical properties of steam as having high heat capacity to reduce local flame temperature, and hence reduce emissions by inhibiting thermal NOx forward reaction rate. In this work, ultra-high steam content with steam-to-air mass ratio up to 40% is premixed with methane air mixture before entering a swirl-stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…It is worth pointing out that this burner configuration has previously been studied numerically on the wet combustion of methane [33,32,34]. The setup of mesh and boundary conditions generally follows the previous work.…”
Section: Mesh and Boundary Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth pointing out that this burner configuration has previously been studied numerically on the wet combustion of methane [33,32,34]. The setup of mesh and boundary conditions generally follows the previous work.…”
Section: Mesh and Boundary Conditionsmentioning
confidence: 99%
“…Li et al [27,28] studied MILD combustion using LES/PaSR model and found that autoignition and flame-like structures both play important roles in the combustion. Duwig's group conducted a sequence of works [29,30,31,32,33,34]. Duwig et al studied a propane-air fuelled flameless burner using LES with detailed chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al [27,28] studied MILD combustion using LES/PaSR model and found that autoignition and flame-like structures both play important roles in the combustion. Duwig's group conducted a sequence of works [29,30,31,32,33,34]. Duwig et al studied a propane-air fuelled flameless burner using LES with detailed chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…The present work is one of a series of studies [32,33,34] focusing a better understanding of wet combustion technology and its application in gas turbines. This paper aims to fill in these knowledge gaps to facilitate the use of methanol in gas turbine and better understand the combustion properties of large alcohols.…”
Section: Introductionmentioning
confidence: 99%